Hubungan Antara Penerapan Sanitasi dengan Tingkat Kepuasan Pembeli di Rumah Makan di Pantai Depok Bantul - Wulan Wahyuningsih; F.X. Amanto Rahardjo; Lilik Hendrarini (Poltekkes Kemenkes Yogyakarta, 2013)
Restaurants appear and develop in line with consumers needs. Therefore, if they are not sup-ported with good application of sanitation, the existence of restaurants may contribute to health problem such as food poisoning as well as the spread of gastrointestinal disease, for example, diarrhoea. The study was aimed to understand the relationship between the application of sani-tation among restaurants in Depok Beach of Bantul and comsumers’ satisfaction by conducting a cross sectional survey. A hundred visitors of five chosen restaurants in the beach were interview-ed as the respondents. The results showed that three out of the five restaurants had reach the good quality of sanitation and the majority of the respondents (61 %) satisfied with the sanitation condition. The chi-square statistical test revealed that there is a relationship between the applica-tion of sanitation and consumers’ satisfaction (p value < 0,001). Based on the those results, it is advised for the owners of the restaurants which were already healthy to maintain the good condi-tion and for those whose restaurants were not, to make an improvement. For tourism agency and health officers, it is advised as well to do and to up-level a periodical health education which consist of the importance of providing good sanitation and periodical sanitation inspection by should also be scheduled.